PEMBERDAYAAN MASYARAKAT DUSUN SOBAYAN (KARANGANYAR) MELALUI SOSIALISASI BANK SAMPAH DAN KOMPOS DALAM UPAYA PENGOPTIMALAN PEMANFAATAN LINGKUNGAN DI MASA PANDEMI - Ayunia N Zahro; Elizabeth S.A.V. Arnanda; Ahmad Z Wirakusuma; Candra T Pradipta; Febriyani F Rachmawati; Citra M Amara; Elsi P Katyagni; Himawan A Himawan A; Andhi G Maranta; Susantiningrum Susantiningrum (Prosiding Seminar Nasional Unimus, 2021)
The introduction to Waste Banks and Organic Fertilizer that took place in Dusun Sobayan, DesaBrujul, Kecamatan Jaten, Kabupaten Karanganyar aimed to increase awareness and provideinsights to the local residents in solving waste problems that supposed to be done in their respectiveresidences. This program was supported by the head of Dusun Sobayan along with its functionariesand respected figures, and Waste Bank Team of UNS as the speakers. This program took placealongside a routine meeting of Dusun Sobayan, and of course applying the health protocol regardingthe Covid-19 pandemic. The participants of this program were enthusiastic following the series ofevents, seen from the way the participants actively asking interesting questions to the speakers. Thisintroduction gave the participants new knowledge about the waste problems, and the way their wastecan be converted into real money or gold. With this program, the local residents of Desa Brujul areexpected to pay more attention regarding the waste problems around their residents and the village isexpected to be a model for its waste management and recycling.  Keyword : Waste bank, Organic fertilizer